Tail dependence of a pareto process - Ferreira, Marta Susana (2012)
Heavy-tailed autoregressive processes defined with minimum or maximum operator are good alternatives to classic linear ARMA with heavy tail noises, in what concerns extreme values modeling. In this paper we present a full characterization of the tail dependence of the autoregressive minima process, Yeh-Arnold-Robertson Pareto(III).